The interplay of brand identification, satisfaction, and psychological well-being: a mediational role of positive WOM behavior in higher education - Aslan, Melda; Aslan, Harun (Springer Science and Business Media LLC, 2025)
BACKGROUND: This study explores the interplay between department brand identification, student satisfaction, and psychological well-being among social work students. It also examines the mediating role of positive word-of-mouth (PWOM) behavior to understand how these factors interact. By fostering a sense of identity and satisfaction, universities can enhance students’ well-being and institutional loyalty. METHODS: A cross-sectional study design was employed with a sample of 401 undergraduate students selected through convenience sampling. Structural equation modeling (SEM) was used to analyze the relationships among department brand identification, student satisfaction, psychological well-being, and the mediating effect of PWOM behavior. RESULTS: Findings revealed that PWOM fully mediates the relationship between department brand identification and psychological well-being, suggesting that a strong sense of departmental identity influences mental health through advocacy behaviors. Additionally, PWOM partially mediates the relationship between student satisfaction and psychological well-being, indicating both direct and indirect effects of satisfaction on mental health. These results highlight the importance of fostering a cohesive departmental culture to enhance students’ emotional connections, satisfaction, and advocacy behaviors. CONCLUSIONS: The study underscores the strategic role of student satisfaction in promoting psychological well-being and institutional loyalty. By encouraging positive experiences and a sense of belonging, universities can support students’ resilience and engagement. Future research should explore these relationships in different academic settings and employ longitudinal designs to provide deeper insights.
Keywords: Quality education; Research; Positive word-of-mouth behavior; Psychology; Higher education; Psychological well-being; Student satisfaction; Department brand identification; BF1-990